2004
DOI: 10.1038/sj.ijir.3901272
|View full text |Cite
|
Sign up to set email alerts
|

Penile measurements in normal adult Jordanians and in patients with erectile dysfunction

Abstract: The purpose of this work was to determine penile size in adult normal (group one, 271) and impotent (group two, 109) Jordanian patients. Heights of the patients, the flaccid and fully stretched penile lengths were measured in centimeters in both groups. Midshaft circumference in the flaccid state was recorded in group one. Penile length in the fully erect penis was measured in group two. In group one mean midshaft circumference was 8.9871.4, mean flaccid length was mean 9.371.9, and mean stretched length was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 15 publications
8
40
1
3
Order By: Relevance
“…7 The mean flaccid penile length reported from Nigeria 8 is 8.16 and from Israel 9 8.3 cm, which are similar to the findings of the present study without any significant difference.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7 The mean flaccid penile length reported from Nigeria 8 is 8.16 and from Israel 9 8.3 cm, which are similar to the findings of the present study without any significant difference.…”
Section: Discussionsupporting
confidence: 82%
“…This goes consistent with the findings of the present study. Awwad et al 7 also found significant correlation between height and midpoint circumference, but could not find any relationship with flaccid or stretched lengths. Present study shows that BMI has a significant inverse correlation with flaccid, stretched and erected lengths (Po0.01), which goes consistent with the findings of Ponchietti et al 6 But in the present study, BMI is found to have a positive correlation with flaccid circumference (Po0.01) unlike what is reported by Ponchietti et al 6 Although weight is found to be positively correlated with erected circumference and BMI, very significant (Po0.01) inverse relationship was found with flaccid and stretched lengths.…”
Section: Discussionmentioning
confidence: 91%
“…The authors cited loss of elasticity and lack of intermittent stretching of tunica albuginea as one explanation for the disparity in penile length between potent men and impotent men. 14 Probably the most common etiology of penile shortening is seen in patients with Peyronie's disease. It is important to note that both the natural history of disease and the scarring process after surgical repair with incision/excision of plaque with graft or a penile plication procedure for surgical correction may cause a reduction in penile length.…”
Section: Conditions Causing Penile Shorteningmentioning
confidence: 99%
“…[12][13][14] However, it is still too soon to establish an average penis size for each average height range or any other characteristic, since no significant associations were found. In fact, Lever et al 15 investigated this issue using the internet, with more than 50,000 participants, and found that 12% thought that their penises were small, while 22% thought that their penises were large and 55% said that they were satisfied with their penis size.…”
Section: Resultsmentioning
confidence: 99%